The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1002/1521-4141(200012)30:12<3562::aid-immu3562>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Expression of functional CD8α β heterodimer on rat γ δ T cells does not correlate with the CDR3 length of the TCRδ chain predicted for MHC class I-restricted antigen recognition

Abstract: In accordance with their lack of MHC restriction, most mouse and human γ δ T cells express neither the CD4 nor CD8(α β) coreceptor. In striking contrast, up to 80% of splenic rat γ δ T cells express the CD8α β isoform of CD8, which for the α β T cell subset serves as a marker for MHC class I‐restricted cells. We compared CD8 on α β and γ δ T cells with regard to co‐stimulatory function and correlation of CD8 expression with TCRDV usage and CDR3δ length. In both subsets, CD8 acted as a co‐stimulatory molecule i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…In our study, we observed that a portion of ␥␦ T cells expressed CD8␣␤ as previously described in rats (34). The CD8 appeared to be functional and not restricted to oligoclonal ␥␦ T cells.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, we observed that a portion of ␥␦ T cells expressed CD8␣␤ as previously described in rats (34). The CD8 appeared to be functional and not restricted to oligoclonal ␥␦ T cells.…”
Section: Discussionsupporting
confidence: 82%
“…cyte kinase (Lck) association of the CD8αβ heterodimers of γδ T-cells was indistinguishable from that of CD8αβ-expressing αβ T-cells.Nevertheless, analysis of CDR3δ lengths of TCRs expressed by the different T-cell types (CD8αβ-positive vs. CD8-negative) showed no difference in length and the average length was even higher than for homologous mouse TCR-δ chains, indicating that these TCRs cannot act in an αβ TCR-like MHC-restricted manner 70. Morerelated to classical MHC-restricted αβ T-cells are recently discovered γδ T-cells with specificity for melanoma antigen recognized by T-cells 1 (MART-1) peptides presented by HLA-A*0201.…”
mentioning
confidence: 99%